Ductal Carcinoma of the Prostate: An Uncommon Entity With Atypical Behaviour. Issue 2 (February 2019) - Bergamin, S.; Eade, T.; Kneebone, A.; Kench, J.G.; Sved, P.; Biset, J.-F.; Hruby, G.
Abstract: Aims: Ductal adenocarcinoma is a rare variant of prostate cancer, and as such clinical outcomes and best management are not well defined. This series demonstrates the atypical presentation and unusual clinical behaviour of ductal adenocarcinoma and proposes management guidelines to assist clinicians. Materials and methods: A retrospective review of pure (nine patients) and mixed (18 patients) ductal adenocarcinoma of the prostate referred to the Departments of Radiation Oncology of the Sydney Cancer Centre, Royal Prince Alfred Hospital and Northern Sydney Cancer Centre, Royal North Shore Hospital, between 2000 and 2015. Results: Twenty-seven patients were treated with definitive radiotherapy, nine patients (33%) with pure ductal and 18 (67%) with mixed ductal-acinar adenocarcinoma. The median follow-up was 38 months. Four patients (15%) failed locally, all of whom received less than 80 Gy, or no brachytherapy boost. Five patients (19%) failed distantly, four with biopsy-proven lung metastases. All distant failures occurred with a prostate-specific antigen (PSA) < 3 ng/ml. Conclusion: This series shows the atypical clinical presentation of this entity, as well as its propensity to metastasise to unusual sites. Relapse may occur at low absolute PSA values and is often asymptomatic. Ductal cancer should not simply be regarded as a high Gleason grade cancer. We propose management guidelines, including regular computed tomography examinations (rather than relying solely on PSA levels) as part of the follow-up for patients with any component of ductal adenocarcinoma. Highlights: Prostate ductal adenocarcinoma commonly presents with haematuria and lower urinary tract symptoms. Radiotherapy is a suitable treatment option for the management of ductal adenocarcinoma. Ductal adenocarcinoma recurs at unusual sites such as the lung. Prostate-specific antigen is not a reliable marker for recurrence.